2005
DOI: 10.1002/ardp.200400929
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity and Studies on Mode of Action of Novel Xanthoxyline‐Derived Chalcones

Abstract: Chalcones and chalcone-like compounds, most of them new ones, prepared by base-catalyzed condensation of appropriate aldehydes and xanthoxyline, were tested for antifungal properties against a panel of yeasts, hialohyphomycetes as well as dermatophytes with the agar dilution assay. Results indicate that neither the sole presence of a "xanthoxyline-like" substitution pattern nor a 2'-OH substituent on ring A are sufficient for these compounds to have antifungal properties. The chalcone 3-(2-chlorophenyl)-1-(2'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 28 publications
6
49
0
6
Order By: Relevance
“…Compounds ( 4 ) and ( 6 ) were not tested towards C. albicans and fungi due to insufficient amount of samples. The antifungal properties of flavokawain A ( 4 ) against Saccharomyces cerevisiae , Candida albicans, and some other fungi were reported to be inactive [24], and these results complement our findings. Compound 4 did not show any inhibition towards Gram-positive and Gram-negative bacteria tested in this study.…”
Section: Resultssupporting
confidence: 89%
“…Compounds ( 4 ) and ( 6 ) were not tested towards C. albicans and fungi due to insufficient amount of samples. The antifungal properties of flavokawain A ( 4 ) against Saccharomyces cerevisiae , Candida albicans, and some other fungi were reported to be inactive [24], and these results complement our findings. Compound 4 did not show any inhibition towards Gram-positive and Gram-negative bacteria tested in this study.…”
Section: Resultssupporting
confidence: 89%
“…The molar ratios of reactants (paraformaldehyde, piperidine, and chalcone) along with the physical data of the compounds 2a-e are presented in the Table 2. The 1 H-NMR, 13 C-NMR, UV, and IR spectra of the compounds 2a -e were in accordance with their chemical structures (Tables 3 and 4). Elemental analyses results (C, H, N) were within 0.4% of the calculated values.…”
Section: Resultssupporting
confidence: 66%
“…Chalcones are a,b-unsaturated ketones, and they are associated with diverse biological activities. Recently, 4-hydroxychalcones have demonstrated their effectiveness as cytotoxic [8,9], antitumor [10,11] antioxidative [10], antibacterial [12], antifungal [13], antileishmanial [14], and antinociceptive [15] agents. Antimicrobial [16] and mosquito repellent [17] activities of orthoaminomethyl phenol derivatives (Mannich phenols) are also noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…CAS against C. albicans ATCC 10231 could be attributed to the fact that FLU action is directed to ergosterol biosynthetic pathway, CAS inhibits cell wall b-glucan synthesis, and 4HMBA inhibits cell transition between yeast-form (non virulent) to filamentous-form (virulent). Boeck et al (2005) have reported hydroxyl chalcones (structurally related to hydroxyl acetophenones) with inhibitory activity on fungal cell wall assembly. Our findings suggest 4HMBA could have an inhibitory effect on the C. albicans cell wall, but the synergistic combination showed by 4HMBA ?…”
Section: Discussionmentioning
confidence: 99%